2010
DOI: 10.1016/j.humpath.2009.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Resected pancreatic adenosquamous carcinoma: clinicopathologic review and evaluation of adjuvant chemotherapy and radiation in 38 patients

Abstract: Summary Pancreatic adenosquamous carcinoma is a rare morphological variant of pancreatic adenocarcinoma with an especially poor prognosis. The purpose of this study is to identify clinicopathologic features associated with prognosis, assess whether the percentage of squamous differentiation in pancreatic adenosquamous carcinoma is associated with an inferior prognosis, and examine the impact of adjuvant chemoradiation therapy on overall survival. Forty-five (1.2%) of 3651 patients who underwent pancreatic rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 28 publications
2
99
2
Order By: Relevance
“…Our group previously reported that adjuvant chemoradiation was associated with improved survival (13.6 months) compared to surgery alone (8.6 months) (10). We reported that adjuvant chemoradiation was associated with improved survival in select subgroups, specifically patients with tumors ≥3 cm in diameter, poor differentiation, lymphovascular or perineural invasion, and squamous component of ≥30%.…”
Section: Adjuvant Therapymentioning
confidence: 81%
See 4 more Smart Citations
“…Our group previously reported that adjuvant chemoradiation was associated with improved survival (13.6 months) compared to surgery alone (8.6 months) (10). We reported that adjuvant chemoradiation was associated with improved survival in select subgroups, specifically patients with tumors ≥3 cm in diameter, poor differentiation, lymphovascular or perineural invasion, and squamous component of ≥30%.…”
Section: Adjuvant Therapymentioning
confidence: 81%
“…One large series of PASC patients failed to demonstrate a significant association between the use of adjuvant radiation or chemotherapy and improved survival; however, this study was unable to account for performance status at the time of treatment (12). On the other hand, our group previously demonstrated a survival benefit with the use of chemoradiation therapy following resection in patients with PASC (10). Additional investigations of the efficacy of adjuvant chemoradiation are limited to anecdotal studies (6)(7)(8)14,(18)(19)(20).…”
Section: Original Articlementioning
confidence: 88%
See 3 more Smart Citations